Roles of raccoons in the transmission cycle of severe fever with thrombocytopenia syndrome virus - TATEMOTO, Kango; ISHIJIMA, Keita; KURODA, Yudai; MENDOZA, Milagros Virhuez; INOUE, Yusuke; PARK, Eunsil; SHIMODA, Hiroshi; SATO, Yuko; SUZUKI, Tadaki; SUZUKI, Kazuo; MORIKAWA, Shigeru; MAEDA, Ken (Journal of Veterinary Medical Science, 2022)
The present study investigated severe fever with thrombocytopenia syndrome virus (SFTSV) infection in raccoons in Wakayama Prefecture from 2007 to 2019. To perform surveillance, an enzyme-linked immunosorbent assay (ELISA) was established, and the sensitivity and specificity of the ELISA were 100% in comparison with a 50% focus-reduction neutralization assay. Using the established ELISA, we performed serosurveillance of SFTSV infection in 2,299 raccoons in Tanabe region, Wakayama Prefecture from 2007 to 2019. The first anti-SFTSV-positive raccoon was captured in October 2009. The seroprevalence of SFTSV infection was <10% between April 2009 and March 2013, 23.9% between April 2013 and March 2014, 37.5% between April, 2014 and March 2015, and over 50% from April 2015. Next, we performed detection of SFTSV genes in sera of raccoons captured in Wakayama Prefecture after April 2013. The results indicated that 2.4% of raccoons were positive for SFTSV genes and that the frequency of SFTSV infection among raccoons between January and March (0.7%) was lower than that between April and June (3.4%). In addition, virus genes were detected from many specimens, including sera and feces of two raccoons, and viral antigens were detected in lymphoid cells in lymphoid follicles in the colon by immunohistochemical staining. In conclusion, SFTSV had recently invaded the area and had rapidly spread among wild animals. The first patient in this area was reported in June 2014, indicating that raccoons are good sentinels for assessing the risk of SFTSV in humans.